The Influence of Competition on Resource Allocation in Preschool Children. Issue 2 (26th June 2016) - Pappert, Anna‐Theresa; Williams, Amanda; Moore, Chris
Abstract: To examine how competition influences resource allocation in 4‐ to 6‐year‐olds, children were assigned to one of two conditions. In the experimental condition children colored a picture for a coloring contest whereas in the control condition they colored a picture to decorate a wall. Subsequently, all children participated in a resource allocation task with another child who was introduced as another participant in the coloring contest or who would also be coloring a picture for the wall. Finally, children were asked how many crayons (out of eight) they wanted to provide to the other child. In the resource allocation task, children made decisions about how to allocate stickers to self and other across four trial types: cost and no cost variations of both advantageous and disadvantageous inequality trials. Children were less prosocial in the experimental condition than in the control condition but only in disadvantageous inequality trials involving a cost. Children in the experimental condition withheld more crayons compared to children in the control condition. These results suggest that competition not only decreases prosocial behavior directly linked to the competition but also decreases generosity when provided with an unrelated resource allocation opportunity.